Kontribusi Penting Pemangku Kepentingan dalam Pengelolaan Perikanan di Rawa Lebak Pampangan - Dina Muthmainnah; Ni Komang Suryati; Khusnul Khotimah (Seminar Nasional Lahan Suboptimal, 2019)
Muthmainnah D, Suryati NK, Khotimah K.  2019. Important contribution of stakeholder for fisheries management of pampangan swamp. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 221-227. Palembang: Unsri Press. Stakeholders are the individuals, groups, or institutions with interest in natural resources at a location, or the person who has the potential to influence activities and provide benefits or losses in the changing conditions. The study aimed to determine the role of stakeholders in the fisheries sector through an ecosystem approach as a component of fisheries management in the Pampangan swamp of Ogan Komering Ilir Regency. This research was conducted in 2016 by collecting the primary data in the field and secondary data from relevant agencies. The research location was Pampangan swamp of Ogan Komering Ilir Regency, South Sumatra Province. There were about ten samples in 10 villages using an opened questionnaire. Data were analyzed by tabulating the stakeholders’ interests and roles. The results showed that the stakeholders were the fishers, fish collector, traders, the government officer, and fish cultivators. Local government plays an important role in determining the management policy for inland fisheries.Keywords: fisheries, management, Pampangan swamp, stakeholder